Copolymer-nanocapsules of zinc phenyl-thio-phthalocyanine and amphotericin-B in association with antimicrobial photodynamic therapy (A-PDT) applications against Candida albicans yeasts - Evangelista, Rodrigo P. [UNESP]; Amantino, Camila F. [UNESP]; Pietro, Rosemeire C.L.R. [UNESP]; Sorrechia, Rodrigo [UNESP]; Piazza, Rodolfo D. [UNESP]; Marques, Rodrigo F.C. [UNESP]; Tedesco, Antonio C.; Primo, Fernando L. [UNESP] (Elsevier, 2021)
Antimicrobial Photodynamic Therapy (A-PDT) is a modern and non-invasive therapeutic modality. Nanostructures like the polymeric nanocapsules (NC) has proved to be a system that has enormous potential to improve current antimicrobial therapeutic practice. NC of Zinc phenyl-thio-phthalocyanine and Amphotericin B association (NC/ZnS4Pc + AMB) built with poly(lactide-co-glycolide) (PLGA) 50:50 using the preformed polymer interfacial deposition method were developed at a 0.05 mg mL− 1 theoretical concentration to improve antifungal activity with two actives association and assistance from PDTa. It showed an average particle diameter of 253.8 ± 17.3, an average polydispersity index of 0.36 ± 0.01, and a negative Zeta potential average of -31.03 ± 5.54 for 158 days. UV–vis absorption and emission spectroscopy analyses did not show changes in photophysical properties in the steady-state of NC/ZnS4Pc + AMB counterparts free ZnS4Pc. The encapsulation percentage of actives was 89.24 % and 7.40 % for ZnS4Pc and AMB, respectively. Cell viability assay using NIH/3T3 ATCC® CRL-1658 ™ cells line showed no cytotoxicity for the concentrations tested. The photodynamic activity assay using NC/ZnS4Pc + AMB diluted showed fungal toxicity against Candida albicans yeast with energetic fluences of 12 J.cm-2 and 25 J.cm-2 by a decrease in cell viability. The MFC assay demonstrated a fungistatic activity for the conditions employed in the PDTa assay. The results show that NC/ZnS4Pc + AMB is a promising nanomaterial for antimicrobial inactivation using PDT.
Keywords: Nanocapsules; Photodynamic therapy; Polymeric nanomaterials; Zinc Phenyl-thio-phthalocyanine